Boosting Sidoarjo youth engagement via participatory communication and targeted capacity building - Kristama, Baswara; Kurniawaty, Yuni; Sunarto, Samuel Kevin; Ramananda, Diki (Jurnal Studi Komunikasi, 2026)
Youth participation in community-based social organisations such as Karang Taruna remains uneven, despite the substantial proportion of young people within local communities. Sidoarjo Regency represents a socially transitional area characterised by strong urban–communitarian dynamics and cultural complexity, with individuals ranging from 15–29 yrs old forming a strategic demographic group for social development. This study examined the effectiveness of empathy-based participatory communication in strengthening youth social participation through a Research Capacity Building (RCB) approach, focusing on Karang Taruna in Sidoarjo Regency. A qualitative participatory action research design was employed, involving in-depth interviews and focus group discussions with 30 purposively selected informants, including youth members, community leaders, and facilitators. The research was conducted across three villages—Gisikcemandi, Masangan Kulon, and Bungurasih—representing diverse socio-cultural contexts. A four-week intervention comprised participatory communication training, social leadership development, and direct involvement in community-based activities. Data were analysed thematically. The findings reveal four interconnected themes: (1) participatory communication patterns within Karang Taruna, (2) the internalisation of empathy values through egalitarian and dialogical interactions, (3) the role of empathetic interventions in enhancing youth confidence, engagement, and critical awareness, and (4) contextual challenges and opportunities in sustaining participatory communication practices. The integration of empathy-based communication with the RCB approach strengthened collective learning, intergenerational dialogue, and sustained social participation. This study concludes that empathy-based participatory communication, when embedded within a research capacity building framework, contributes to the development of a sustainable ecosystem of youth social participation and community-driven social change.